GUIDE TO CHOOSING THE RIGHT AGRI PHOTOVOLTAIC MOUNTING SYSTEM - TABAKOVIC, Momir; Keseric, Mihajlo (Journal on Processing and Energy in Agriculture, 2021)
The aim of this work is to create a guide for the selection and planning of an agri-photovoltaic mounting system. The mounting systems available on the market were analyzed and those that can be used in agri-photovoltaics were selected. Since there are many mounting systems on the market and there are hardly any technical differences between them, four systems were selected and described in this work. The systems are those that almost every manufacturer offers in a modified form. Three of the four systems are produced by the same manufacturer "ZIMMERMANN PV-Stahlbau GmbH & Co. KG", while the remaining system is produced by the manufacturer "Next2Sun GmbH". Through this collected knowledge about mounting systems, it was possible to create a questionnaire, which was then sent to farmers. The online questionnaire was sent via e-mail to the desired target group throughout Austria. It was sent to as many farmers as possible in order to obtain a large database. The data resulting from the questionnaire made it possible to create a guideline to support technicians in the planning of new Agri-PV systems.